Relación entre las transferencias de recursos determinados y el crecimiento económico de la región Loreto en el periodo 2014-2024 - Cabrera Rios, Jhofre Aldair (2025)
This research aims to analyze the relationship between earmarked resource transfers and the economic growth of the Loreto region during the period 2014–2024. A quantitative approach was used, with a correlational scope and a non-experimental longitudinal design. Data were obtained from the Ministry of Economy and Finance (MEF) and the National Institute of Statistics and Informatics (INEI), and processed using statistical tools such as SPSS. The Shapiro-Wilk normality test confirmed that both variables followed a normal distribution (GDP Sig. = 0.973; Transfers Sig. = 0.074), which allowed for the application of Pearson’s Correlation Coefficient. The analysis yielded a correlation coefficient of r = 0.754, indicating a strong positive relationship between earmarked resource transfers and regional economic growth. These findings support the hypothesis that there is a direct and significant relationship between earmarked resource transfers and the economic growth of the Loreto region.